The book on pie : everything you need to know to bake perfect pies - McDowell, Erin Jeanne (Houghton Mifflin Harcourt, 2020)
"100 recipes for perfect pies by Food52 baking consultant, New York Times contributor, and top food stylist Erin Jeanne McDowell"--